In-situ tryptophan-like fluorescence: A real-time indicator of faecal contamination in drinking water supplies. (15th September 2015) - Sorensen, J.P.R.; Lapworth, D.J.; Marchant, B.P.; Nkhuwa, D.C.W.; Pedley, S.; Stuart, M.E.; Bell, R.A.; Chirwa, M.; Kabika, J.; Liemisa, M.; Chibesa, M.
Abstract: Enteric pathogens are typically inferred from the presence of surrogate indicator organisms such as thermotolerant (faecal) coliforms (TTCs). The analysis of TTCs requires time-consuming incubation in suitable laboratories, which can limit sampling resolution, particularly during critical pollution events. Here, we demonstrate the use of in-situ fluorimeters targeting tryptophan-like compounds as a rapid, reagentless indicator of TTCs in groundwater-derived potable water supplies in Africa. A range of other common indicators of TTCs were also determined including nitrate, turbidity, and sanitary risk survey scores. Sampling was conducted during both the dry and wet seasons to investigate seasonality. Tryptophan-like fluorescence was the most effective predictor of both presence/absence and number of TTCs during both seasons. Seasonal changes in tryptophan-like fluorescence in deeper supplies suggest it is transported more efficiently through the aquifer than TTCs. Moreover, the perennial elevated concentrations in some wells suggest it is more resilient than TTCs in groundwater. Therefore tryptophan-like fluorescence could also be a better indicator of some smaller, more easily transported, and long-lived, pathogenic enteric viruses. These sensors have the potential to be included in real-time pollution alert systems for drinking water supplies throughout the world, as well as for mapping enteric pathogen risks in developing regions. Graphical abstract: Highlights: First study to investigate the biological quality of drinking water with technique. Tryptophan-like fluorescence was the best predictor of thermotolerant coliforms. High tryptophan-like concentrations corresponded with high risk potable supplies. Tryptophan-like compounds could be a precautionary indicator of enteric pathogens. Fluorimeters could provide real-time pollution alert systems for potable supplies.